System Cryogenic Supply Cryomagnetic Complex KMK–1000 on the Basis of Micro-Cryogenic Systems of Closed Cicle - Demishev, A.G. (Science and Innovation, 2024)
Introduction. The development of the enrichment industry has identified significant requirements for the development of new technologies and equipment, including the method of magnetic separation. Problem Statement. Advantages of cryomagnetic separation complexes are determined by the efficiency of solving the problem of creating their cryogenic support systems. Purpose. The purpose of this research is to develop a cryogenic supply system (CsC) by solution scientific technical and design and technological problems of cryomagnetic systems creation based on micro-cryogenic closed cycle systems (MCs). Materials аnd Methods. The material of the research is the design of sCs with built-in superconducting magnetic system (SMs) and two MCs. The efficiency of MCs use is determined by the method of thermal balance analysis of their modules. Results. SCS design on the basis of the nitrogen-free cryostat with integrated sMs and two close-cycle MCs and the solution of r&D problems of effective use of the MCs by method of the heat balance analysis of their modules have been proposed. The input units of the MCs modules and neck, as well as the tank, supports and screens are design in such a way as they can operate simultaneously as a system of rigidity and a system of efficient removal of heat from them to the appropriate stages of the MCs modules. The design of sCs provides operation in a stationary mode with a super small supply of liquid helium through the liquid-gas recondensation ring process, in which the gas-liquid helium mixture is an ideal cool conductor. The design of the sCs provides the manufacturability of routine maintenance, even with the change of the modules of the neck and the MCs, without depressurization of the cryostat. Conclusion. Solutions of design and technological, research and technical problems are based on patents of Ukraine N103949 and N88830. The expediency of creation of the complex on the basis of a nitrogen-free cryostat with built-in SMs and two MCs operating in a stationary mode with a very small reserve of liquid helium has been substantiated.